Relative Validity of Administered Indonesian Version of the Short-Form International Physical Activity Questionnaire (IPAQ-SF) among Obese Adolescent Girl Population - Suyoto, Perdana S.T.; Huriyati, Emy; Susilowati, Rina; Julia, Madarina (Pakistan Journal of Nutrition, 2016)
Obesity has raised more concerns in developing countries than ever before as the prevalence continues to increase. Numerous studies seek to learn the role of physical activity in tackling obesity and related health problems. Several methods have been developed to measure physical activity; questionnaire methods are currently the cheapest and fastest compared to the other methods available. However, the validity of the questionnaire used should be a concern for investigators. This study’s objective is to evaluate the relative validity of the Short-Form International Physical Activity Questionnaire (IPAQ) using a 24 h physical activity recall repeated 7 times. Obese adolescent female students were recruited from several junior high schools in Yogyakarta, Indonesia. The students were then administered a 24 h physical activity recall for seven consecutive days. They were also administered the IPAQ-SF. The results from the physical activity recall and the IPAQ-SF were then analyzed statistically to obtain the Spearman correlation coefficient. There was a small but significant correlation between total physical activity from the IPAQ-SF and the physical activity recall r = 0.24). Moreover, vigorous physical activity derived from the IPAQ-SF was also significantly correlated with that of the physical activity recall r = 0.28). Results from the Indonesian version of the IPAQ-SF had a small but significant correlation with physical activity recall. This result showed that the Indonesian version of the IPAQ-SF is a valid method for measuring physical activity among obese adolescent girls.